The influence of SARS-CoV-2 vaccination on in vitro fertilization outcomes - Adi Anis Heusler; Amir Weintraub; Diana Stein; Yael Melamed-Yekel; Sarit Kalfon; Yael Pasternak; David Kulak (Human Vaccines & Immunotherapeutics, 2025)
In December 2020, the FDA granted emergency use approval for 2 separate mRNA vaccines to combat the COVID-19 pandemic. While many questions as to the long-term safety of the vaccine were raised, this was particularly acute for those patients trying to conceive and among those utilizing assisted reproductive technologies. The study aimed to assess the effect of recent mRNA SARS-CoV-2 vaccination on IVF cycle outcomes. A retrospective case-control study, including all IVF patients under the age of 40 years in a hospital-based practice from January 1 to May 31, 2021. The study group included patients who received two doses of the Pfizer/BioNTech vaccine BNT162b2 SARS-COV-2 vaccine between 7 days to 6 months prior to starting IVF. The control group included unvaccinated patients from the same time period in the same year and in 3 previous years. IVF cycle results were compared between the groups. Three hundred and eighty-five women met the inclusion criteria; 349 in the control group and 36 in the vaccinated group. Demographic and clinical characteristics were comparable between the groups. The pregnancy rate was 33.3% (n = 12) in the vaccinated group vs 31.8% (n = 111) in the control group (p > .1). There were no statistically significant differences between the control and vaccine groups. with a small non-significant trend to higher pregnancy rates in vaccinated patients: pregnancy rate OR for vaccination group was 1.17 (95% CI 0.56–2.44). We observed no influence of mRNA SARS-CoV-2 vaccine on patients’ IVF cycle outcomes; vaccination did not change pregnancy rates.